Automatic Toilet Tool Based on Arduino Uno and Sensor Passive Infrared Receiver (PIR) - Nainggolan, Winner P (ETAPs (Journal Electronics, Telecommunication, Electrical, and Physics Science, 2022)
With the development of electronic components so that it can be seen that technological progress is very rapid, the latest innovations are needed in utilizing these technological developments, this can be implemented in the technology of making automatic toilet tools that are very useful for the blind. The toilet is the place most frequented by everyone. However, there are things that are not very easy for the blind to use toiet, due to the factor of not being able to see so that they have difficulty in opening the toilet door and flushing water in the closet automatically, so there is a need for an automatic system and providing information provided in the form of audio sound that there are users of the toilet, In the manufacture of smart toilet automatic tools that can help users among the blind, called smart because it can open the door automatically and turn on the audio sound information and can release water automatically with a dc water pump motor, this is because it uses PIR and infrared sensors as a detector of the presence or absence of toilet users controlled by Arduino Uno, if there is a toilet user, Arduino Uno will process and command the audio will provide information in the form of sound and Motor DC water pump releases water automatically, then if the user has left the toilet and the infrared sensor no longer detects, then Motor DC water pump does not release water. After some analysis and testing, the results show that all functions run as expected. This smart toilet system can be implemented in an actual toilet without having to change the previous conditions at a small cost.